Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1590/s0080-623420140000600013
|View full text |Cite
|
Sign up to set email alerts
|

Caring for family caregivers: An analysis of a family-centered intervention

Abstract: Objective To assess the effectiveness of Problem-Solving Therapy (PST) on family caregivers through the use of scales to measure anxiety, depression and emotional distress; and to explore facilitating factors and obstacles for its use based on the narrative of nurses. Method A clinical trial and an exploratory focus group with the use of mixed analysis methodology. The study was conducted in a primary health care center in Tarragona, Spain, and the sample consisted of 122 family caregivers who were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
9

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 12 publications
0
14
0
9
Order By: Relevance
“…It is crucial to take advantage of this diagnosis, in order to introduce changes in the approach to caregivers, thereby facilitating their role in the family environment. Providing this attention to caregivers will promote personal and family health for dependents cared for at home (20) .…”
Section: The Importance Of Support -Emotional and Interpersonal Needsmentioning
confidence: 99%
“…It is crucial to take advantage of this diagnosis, in order to introduce changes in the approach to caregivers, thereby facilitating their role in the family environment. Providing this attention to caregivers will promote personal and family health for dependents cared for at home (20) .…”
Section: The Importance Of Support -Emotional and Interpersonal Needsmentioning
confidence: 99%
“…In this sense, we found that disease and disability are experiences that represent one of the main challenges to families. The psychosocial problems caused by a person with dependence has impact on the whole family system (7) . The hospital environment/space has its meaning established through the values and beliefs of a culture.…”
Section: Discussionmentioning
confidence: 99%
“…The imagery corresponds to this world of meanings, ideas, fantasies, evocation of figures perceived or not, beliefs, and values where the human being is immersed (8) . A hospital environment involves linkages, accountability, and compassion (7) . In this way, changing the relations in these spaces is joined with the intrinsic characteristics of the environment that is on the baseline of knowledge and emotional phenomena, in a situation where one is connected to the other and, at the same time, lives with the other, where everything is dependent and interdependent, in an empathic relation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And that caregiver's female profile is a reality in different countries, as pointed out by a study conducted in Tarragona, Spain: mostly women assume the role of family caregivers of patients, which puts them at high risk, stress and uncertainties, needing for support in their work. 15 In this context, it's highlighted the role of the family, considered key piece in the patient's recovery process after cardiac surgery, both during hospitalization and in the post-discharge, by being the main source of information and emotional bond with the patient -helping him to face insecurity and experienced stress. This therapeutic relationship can be maximized when there is an interest on the part of health professionals to value the emotional relationship between the family and the patient.…”
Section: Discussionmentioning
confidence: 99%